(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
ملخص تهدف هذه الدراسة الى تصنيف و تحليل تسميات المدارس على أساس أنها مظهر من مظاهر الهوية المؤسسية، يمكن من خلالها التعرف على أبعاد الهوية الاجتماعية و ذلك عبر تصنيف و تحليل لتسميات مدارس مقاطعة غرداية نموذجا، وخلصت الدراسة إلى أن تسمية المدارس هي مظهر للهوية المؤسسية و تؤشر فعلا إلى أبعاد الهوية الاجتماعية للمجتمع المحلي. كلمات دالة : الهوية الاجتماعية، الهوية المؤسسية،المدرسة ،الشخصية Abstract This study aims to classify and analyze schools naming on the basis that they are a manifestation of institutional identity, through which it is possible to identify the dimensions of social identity through classification and analysis of the names of schools in the province of Ghardaia as a model, the study concluded that naming schools is an aspect of the institutional identity and actually indicates the dimensions of the social identity of the local community. Key words: Social identity, institutional identity, school, Personality